Postawa Stanów Zjednoczonych wobec aneksji Krymu przez Rosję i wojny w Donbasie w perspektywie pozimnowojennej – konflikt wartości w tle konfliktu interesów - Jureńczyk, Łukasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject of the analysis is the attitude of the United States towards the annexation of Crimea by Russia and the war in Donbass in the post-Cold War era perspective regarding the conflict of values and interests. The article consists of two main parts. The first of these discusses the policy of the United States towards Ukraine and Russia after the Cold War. During the analysis, considerable attention was paid to the interests that the United States had towards the region of Eastern Europe, as well as the values of peace, stability and democracy promoted there. The second part of the article is devoted to the US reaction to Russia’s unlawful actions in the Crimea and Donbass, undermining the core values and principles of the international community, i.e. independence, sovereignty and territorial integrity of states. It analyzed the strategy of the United States’ response to the crisis in Ukraine, including its activities in the political, economic and military spheres. The analysis was to enable the answer to two basic research questions. First of all, were the principles of the international community violated by Russia and also the interests of the United States in Eastern Europe and the democratic values promoted in the region sufficient reason for Washington to take decisive action in defense of Ukraine? Secondly, are the actions taken by the US in cooperation with the international community enough to force Russia to change its policy towards Ukraine? The answer to both of the questions is negative. Russia’s actions in Ukraine did not undermine the vital interests of the United States, which is why it did not decide to resort to military solutions. The values promoted by Americans also were not a sufficient reason to use more decisive means of response. Washington’s moderate actions have negative consequences for Russia, but they are unable to force it to change its policy towards Ukraine. This is due to the importance of Moscow’s interests in Ukraine, which are particularly important in the context of rebuilding Russia’s superpower status and ensuring a safe and friendly neighborhood. Although the United States does not want to escalate the conflict excessively, its actions have deepened the negative trend in the development of relations between Moscow and Washington observed for almost two decades.